Characterization of arabidopsis mutants altered in their ability to express BABA-induced resistance (BABA-IR) and priming - (:unkn) unknown (My University, 2025)
Plants treated with the non-protein amino acid beta-aminobutyric acid (BABA) develop an enhanced defensive capacity against a large variety of biotic and abiotic stresses. The expression of this BABA-induced resistance (BABA-IR) coincides with a faster and stronger defense response following pathogen attack or abiotic stress. This phenomenon has been termed as priming or potentiation, the underlying mechanism though is unknown. Priming could be based on the accumulation of signalling proteins in an inactive form that would then be activated upon exposure to stress. Another possibility is the accumulation of transcription factors in primed plants leading to an enhanced defence gene transcription when this plant is stressed. A further idea suggests that priming might occurs at the epigenetic level via changes in chromatin structure. Based on the observation that high amounts of BABA induce sterility in Arabidopsis, we have isolated mutants from a population of T-DNA mutagenized Arabidopsis with impaired BABA-induced sterility (ibs) phenotype. In this proposal we plan to concentrate on mutants ibs1 and ibs6. The function of several IBS genes in the defense signaling network of Arabidopsis has been elucidated by testing their reactions towards different biotic and abiotic stresses at the phenotypic and molecular level. Our data so far demonstrate that BABA-IR against biotic and abiotic stresses is based on priming of distinct defense signaling mechanisms involving salicylic acid-, abscisic acid-, and phosphoinositide-dependent pathways and that callose deposition plays an important role in BABA-IR. We propose first to get a more complete picture concerning the role of callose and vesicle transport in BABA-IR by further characterizing the ibs6 mutant. Additionally, the role of IBS1in priming will be investigated. Protein partners directly interacting with the protein kinase IBS1 will be determined and characterized. Possible substrates for IBS1 will be sought for . We will be using microarray technology to obtain a detailed knowledge of IBS1-dependent gene expression. Finally, we plan to further pursue our recent discovery that IBS1 messenger RNA can be postranscriptionally regulated and investigate the implications for priming. The results of the described research will lead to a better understanding of the priming phenomenon in plants. Additionally, they might eventually help to devise new stragegies in agronomy since priming-inducing agents confer enhanced resistance against biotic and abiotic stresses with minimal inhibitory effects on commercially important traits.
Keywords: Induced resistance; beta-aminobutyric acid; priming; potentiation; resistance; Arabidopsis